2015
DOI: 10.1111/jocn.12998
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and psychosocial correlates of sexual activity in older Chinese people

Abstract: Frontline health professionals need to be aware of the growing needs for sex education in older persons, particular attention should be paid to discuss the limitations brought about by various chronic conditions associated with ageing and their relevance to elder sexuality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 21 publications
(27 reference statements)
2
9
0
8
Order By: Relevance
“…With increasing age, physical health, sexual desire, and sexual capacities decrease that would affect sexual frequency. 6 , 34 However, low or high frequency in one person means they have less or strong interest in sex, and then age factors have different effects in different frequencies. 9 Similarly, gender also plays an important role in the frequency with which people engage in sex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With increasing age, physical health, sexual desire, and sexual capacities decrease that would affect sexual frequency. 6 , 34 However, low or high frequency in one person means they have less or strong interest in sex, and then age factors have different effects in different frequencies. 9 Similarly, gender also plays an important role in the frequency with which people engage in sex.…”
Section: Discussionmentioning
confidence: 99%
“…A positive association between sexual knowledge and coital frequency has been previously reported in aging. 38 , 39 Yang and Yan 34 showed that sufficient knowledge of sexuality predicted a higher level of sexual activity in older Chinese people. Interestingly, in our research of internal migrant populations, sexual knowledge had a positive effect in 10% and 50% quartile of frequency, but had a negative effect in 90% quartile.…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study shows that 41.26% of women reported engaging in some form of sexual activity in China. [ 21 ] Therefore, 72.9% of patients had no sexual activity, 22.0% considered that there was no effect on their sexual life, 4.2% considered that there was “a little” effect, and 0.9% considered that there were some effects (Supplementary Table 3). There were no differences between the 2 groups (all P > .05) (Supplementary Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Otros estudios evidenciaron que, los polacos tienen actitudes moderadas hacia la sexualidad (Cybulski et al, 2018) y el 53% de AM españoles consideraron la importancia de la sexualidad (Hernández et al, 2019). En China, Yang & Yan (2016) afirman que la mitad de la población de AM mantienen una actitud de interés hacia lo sexual. DeLamater (2012), Kleinstäuber (2017) y Beckman et al, (2014) proponen que la actitud hacia lo sexual tiene relación directamente proporcional con el interés sexual, la frecuencia de la actividad (Traeen et al, 2018), el deseo (Trudel et al, 2014), la expresión sexual (Da Torres & Rodríguez, 2019), la satisfacción sexual (Cybulski et al, 2018) y menor percepción del envejecimiento (Da .…”
Section: -5459unclassified
“…A su vez, tener pareja estable y satisfacción relacional son determinantes de la frecuencia de las conductas sexuales (Gharibi et al, 2019;Jalenques et al, 2020;Perdomo et al, 2013). El estatus civil de casado es decisivo únicamente en mujeres (Yang & Yan, 2016).…”
Section: -5459unclassified